A new species of the subgenus Troginus Mulsant et Rey 1878 (Coleoptera: Staphylinidae: Oxytelinae: Carpelimus) from Borneo - Gildenkov, Mikhail Yu. (Zootaxa, 2018)
Carpelimus (Troginus) varius Gildenkov, sp. n. (Coleoptera: Staphylinidae: Oxytelinae) from Borneo (Malaysia, Sabah) is described and illustrated.